PERANCANGAN REAKTOR BIODIESEL DARI LIMBAH MINYAK GORENG SISTEM BATCH SEMIOTOMATIS - M. Hasan Abdullah; Subaderi Subaderi (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2022)
The invention relates to the design of a reactor for producing biodiesel. This reactor consists of three process, reactor tubes (esterification and transesterification processes), washing tubes (washing and settling), and drying-evaporating tubes. This reactor is designed to process used cooking oil which contains high free fatty acids into biodiesel with a batch system. In operation, this reactor is equipped with a DC motor, stirrer, heater, DC pressurized pump, sprayer, and condenser. Additional devices are installed such as speed control, thermocouple, and timer so that the reactor can be operated automatically. The method of the present invention begins with an esterification reaction in which the molar ratio of oil and methanol is 1: 6 using an H2SO4 catalyst of 3% by weight of oil. Reflux treatment with a temperature of 50ºC at a speed of 300 rpm for 60 minutes. The results of the esterification process are then allowed to stand for one hour and the triglycerides are separated. For the transesterification process, the molar ratio of oil and methanol is 1: 6 using a NaOH catalyst of 0.5% by weight of oil. Reflux treatment with a temperature of 60ºC at a speed of 400 rpm for 60 minutes. Then it was allowed to stand for one hour and the biodiesel and glycerol were separated. The biodiesel is then washed with 50ºC warm water by spraying. After the washing process, it is then heated to a temperature of 110ºC. This method is able to convert used cooking oil waste into biodiesel with 95% yield and acid number below 0.5 mg-KOH/g (according to SNI 7182-2015 standard).